Barrier to the EU membership: The institutional discrimination of minority groups in Bosnia and Herzegovina - Brljavac, ﻿Bedrudin (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿Although Bosnia and Herzegovina (BiH) has been going through extensive European Unionisation over the last 10 years the country is still facing serious democratic deficit. In particular, the post-Dayton public sphere has been dominated by ethno-nationalist political elites who are doing everything they can to exclude non-nationalists and members of minority groups from the decision-making process. This is a nagging paradox since one of the main objectives behind the integration of the European countries into the European Community was to reduce disintegrative and dangerous influences of nationalists to establish peaceful, prosperous, and secure community. This article examines how the process of the post-Dayton ethno-nationalization has resulted in widespread discrimination against the so-called Others as they are defined in the Constitution. In the post-war BiH democratic participation has turned into a competition between the three ethnic communities, Bosniaks, Serbs, and Croats, rather than between individual nationalities having equal rights of vote. This is why Bosnian people are still living under a political system which is closer to ethno-democracy or ethnocracy rather than a democratic regime. Under such discriminatory regime BiH cannot enter the European Union which is a model of open and democratic society.